A high temperature electroplated ceramic mosaic and its production process
Through the high-temperature electroplating process, combined with the design of the UV layer and the high-temperature coating bonding layer, the problem of short service life, non-scratch resistance and fading is solved, and higher adhesion and durability are achieved.
Patent Information
- Application Number
- CN202411923065.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Existing electroplated ceramic mosaic products have short service life, are not scratch-resistant and are prone to fading.
Using high-temperature electroplating technology, a UV layer is formed by pretreating the ceramic body, followed by spraying the coating slurry and firing at high temperature to form a high-temperature coating bonding layer, and then magnetron sputtering is electroplating under vacuum conditions, and finally coloring is carried out by magnetron sputtering.
It improves the adhesion between the electroplating layer and the ceramic blank, enhances the scratch resistance and service life of the ceramic mosaic, and ensures that the color is bright and not easy to fade.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electroplating ceramics, and in particular relates to a high-temperature electroplating ceramic mosaic and a production process thereof. Background Art
[0002] Ceramic mosaic is a traditional mosaic handicraft, a material composed of small ceramic tiles fired from clay, which has the advantages of fire resistance, frost resistance, water resistance, non-slip and easy cleaning, and is durable and inexpensive. As a traditional and practical decorative material, ceramic mosaic occupies a relatively important position in modern architecture and interior design.
[0003] Electroplating can be used to further decorate and beautify ceramic products. After electroplating, coatings of various colors or patterns can be formed on the surface of ceramic mosaics, thereby improving the ornamental value and market competitiveness of ceramic mosaics and meeting people's more diverse needs.
[0004] However, the existing electroplated ceramic mosaic products or electroplated small-sized ceramic products are all produced at low temperatures. The production process is mostly to first use an oven to dry the moisture, and then enter the vacuum electroplating furnace for low-temperature electroplating at 150°C. Although the products obtained in this way can reduce the internal stress of the coating and improve the stability of the coating compared to high-temperature electroplating, the products obtained by low-temperature electroplating have a short service life and are easy to fade. Many ceramic products have poor bonding with the vacuum coating and poor scratch resistance. Summary of the invention
[0005] The object of the present invention is to provide a high-temperature electroplated ceramic mosaic and a production process thereof, so as to solve the problems of short service life, poor scratch resistance and easy discoloration of electroplated ceramic products.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The present invention provides a production process for high-temperature electroplating ceramic mosaics, comprising the following process steps:
[0008] S1. Pretreatment: After the ceramic body is cleaned and dried, a UV coating is sprayed on the surface of the body, and a UV layer is formed after drying and curing to obtain a pretreated ceramic body;
[0009] S2. High temperature coating: spraying the coating slurry on the obtained pretreated ceramic body UV layer, drying and removing water, and then firing at high temperature to form a high temperature coating bonding layer;
[0010] S3. Electroplating: Under vacuum conditions, the ceramic body obtained in step S2 is subjected to metal bombardment and adhesion on the surface of the high-temperature coating bonding layer by magnetron sputtering to form an electroplated metal layer;
[0011] S4. Coloring: By controlling the type of electroplating auxiliary gas, the surface of the electroplated metal layer of the ceramic body obtained in step S3 is colored by magnetron sputtering metal titanium to form an electroplated coloring layer, and finally a high-temperature electroplated ceramic mosaic is obtained.
[0012] Preferably, the high temperature firing temperature in the S2 high temperature coating step is 800-900°C.
[0013] Preferably, in the S3 electroplating step, the vacuum degree is 10-7 to 10-3 mbar, the magnetron sputtering temperature is 600 to 800°C, and the sputtering time is 40 to 90 min.
[0014] Preferably, the metal layer in the S3 electroplating step is one of a titanium layer, a nickel layer, a cobalt layer and an iron layer.
[0015] Preferably, the auxiliary gas includes one of oxygen, argon and nitrogen.
[0016] Preferably, the sputtering time in the S4 coloring step is 2 to 6 minutes.
[0017] Preferably, the thickness of the UV layer is 8-12 μm; the thickness of the high-temperature coating bonding layer is 0.1-0.2 mm; the thickness of the electroplated metal layer is 0.1-0.3 μm; and the thickness of the electroplated coloring layer is 1-3 μm.
[0018] By adopting the above technical scheme, the high-temperature electroplated ceramic mosaic obtained by the present invention is a multi-layer structure. After pretreatment, the ceramic surface is smooth and free of impurities, has strong reaction activity, and can be tightly combined with the high-temperature coating bonding layer during high-temperature firing. Further, high-temperature electroplating treatment can be performed. Since there is a high-temperature coating bonding layer between the ceramic body and the electroplating layer, the stress generated under high temperature can be eliminated, thereby solving the problem of poor stability of the original high-temperature coating structure and improving the adhesion between the electroplating layer and the ceramic substrate.
[0019] In the electroplating process, the vacuum degree of the electroplating is adjusted. At the same time, under high temperature conditions, the diffusion and deposition of metal ions can be promoted, and the deposition of metal ions becomes more orderly, and smaller and more uniform grains can be formed, making the obtained electroplated metal layer denser, and the mechanical strength is also improved. The bonding force between the coating and the substrate is also significantly improved, which can significantly improve the scratch resistance and service life of the obtained ceramic mosaic.
[0020] Finally, by adjusting the type of auxiliary gas, for example, in a nitrogen atmosphere, titanium can be magnetron sputtered to make the ceramic mosaic material appear golden, in an argon atmosphere, it reacts to obtain silver, and in an oxygen atmosphere, it can obtain colorful ceramic mosaic products. The ceramic mosaic obtained by this method has bright colors, simple process steps, is not easy to fade, and can significantly increase the service life of the material.
[0021] Preferably, the raw materials of the UV coating include UV paint, photoinitiator and diluent in a mass ratio of 1: (0.4-0.5): (1-1.2).
[0022] Preferably, the UV paint includes one of epoxy acrylate resin and polyurethane acrylate resin.
[0023] Preferably, the photoinitiator includes a combination of one or more of diaryliodonium salts, triarylsulfonamide salts, benzildialkylketal, benzoylformate photoinitiators and acylphosphine oxide photoinitiators.
[0024] Preferably, the diluent includes a combination of one or more of glyceryl trimethacrylate, glyceryl triacrylate, hexamethylene diisocyanate diacrylate, 2-hydroxyethyl methacrylate, benzene diacrylate, ethyl acrylate and diethylene glycol diacrylate.
[0025] By adopting the above technical solution, the ceramic body is pretreated before being electroplated, and a UV layer is sprayed on the surface of the body. During the drying and curing process of the UV layer, especially during the photocuring process, the irradiation treatment will eliminate the pollutant molecules on the ceramic surface, thereby reducing the impact of the pollutants on the subsequent coating.
[0026] And after pretreatment, the UV layer formed on the surface of the ceramic body can significantly improve the hydrophilicity of the ceramic body surface, forming a highly reactive surface, thereby improving the adhesion between the high-temperature coating bonding layer and the ceramic body, and further improving the scratch resistance of the ceramic mosaic material.
[0027] Preferably, the raw materials of the coating slurry include a frit, an aqueous oil and a metal oxide in a mass ratio of 1: (1.2-1.8): (0.05-0.1); the metal oxide is an oxide of iron and / or manganese.
[0028] Preferably, the metal oxide includes a combination of one or more of ferrous oxide, manganese oxide and iron oxide.
[0029] Preferably, the frit is a lead-free frit glaze.
[0030] By adopting the above technical solution, a high-temperature coating bonding layer exists between the electroplating layer and the ceramic body of the present invention, which can greatly improve the adhesion between the electroplating layer and the ceramic body, and improve the service life and scratch resistance of the ceramic mosaic material. Specifically, the raw materials of the high-temperature coating bonding layer of the present invention mainly include frit, aqueous oil and metal oxide.
[0031] The mixture of frit and aqueous oil is conducive to uniform spraying on the surface of ceramic body. After drying, the aqueous oil gradually evaporates, leaving a pore structure. Then, after high-temperature sintering, the frit molecules continue to move to form a molten zone, which can further promote the rearrangement of materials and the formation of voids. The high-temperature coating bonding layer formed after high-temperature sintering has a complex pore structure, which can be interconnected through tiny channels to form a continuous network. The pore structure is conducive to the penetration of electroplated metal into the bonding layer, thereby improving the adhesion of the electroplated metal layer on the ceramic body.
[0032] At the same time, the raw materials of the high-temperature coating bonding layer also include metal oxides, that is, iron or manganese oxides or oxide compositions. The addition of metal oxides can combine with the electroplated metal ions under vacuum and high temperature conditions, and the electroplated metal can combine with the exposed metal oxides through the pores of the bonding layer, thereby further enhancing the bonding force between the electroplated metal layer and the bonding layer, improving the adhesion between the electroplated metal layer and the ceramic body, and increasing the scratch resistance of the obtained ceramic mosaic material.
[0033] Preferably, the raw materials of the coating slurry also include polyborosiloxane; the mass ratio of the polyborosiloxane to the frit is (0.3-0.4):1.
[0034] Preferably, polyborosiloxane is prepared according to the following method:
[0035] Methyltrimethoxysilane and boric acid are mixed, the temperature is raised to 30-40°C, the mixture is stirred for 1-2 hours, and then the temperature is raised to 80-120°C, the reaction is continued for 4-8 hours, and the glue is obtained by filtration, and finally polyborosiloxane is obtained by drying and heat treatment. The heat treatment temperature is 150-250°C and the heat treatment time is 2-4 hours.
[0036] More preferably, the molar ratio of boric acid to methyltrimethoxysilane is (0.2-0.4):1.
[0037] By adopting the above technical solution, polyborosiloxane is a polymer with a cross-linked network structure, which has good compatibility with the frit and contains a flexible siloxane main chain. When added to a mixture of the frit and aqueous oil, it can improve the dispersibility of the frit and metal oxides in the aqueous oil, so that the coating slurry can be evenly coated on the surface of the ceramic body, forming a high-temperature coating bonding layer with uniform thickness and uniform particle distribution.
[0038] And because polyborosiloxane has a main chain with a cross-linked network structure, it can better coordinate the bonding between the frit and the metal oxide. After high-temperature sintering, it can help regulate the formed pore network and form micro-nano channels. While providing the channel structure, it improves the structural density of the high-temperature coating bonding layer, thereby improving the bonding force and mechanical strength of the ceramic surface coating. It will not hinder the penetration deposition of the electroplated metal, and can also help expose more active sites and strengthen the bonding force between the high-temperature coating bonding layer and the electroplated metal layer.
[0039] In a second aspect, the present invention provides a high-temperature electroplated ceramic mosaic, which is produced according to the above-mentioned production process of the high-temperature electroplated ceramic mosaic.
[0040] Beneficial effects of the present invention:
[0041] 1. The ceramic mosaic provided by the present invention adopts high-temperature electroplating. Under vacuum conditions, high temperature promotes the diffusion and deposition of metal ions, and can form a dense electroplated metal layer. Under the action of the high-temperature coating bonding layer, the problem of poor structural stability of the high-temperature coating can be solved, and the adhesion between the electroplating layer and the ceramic body can be improved, thereby improving the scratch resistance and service life of the ceramic mosaic.
[0042] 2. The raw materials of the coating slurry used in the present invention include frit, aqueous oil and metal oxide. The aqueous oil is combined with the frit, so that the obtained high-temperature coating bonding layer has a complex pore structure and forms a continuous network, which is conducive to the penetration of electroplated metal ions. The metal oxide can be combined with the electroplated metal ions under vacuum high-temperature electroplating, thereby improving the bonding force between the electroplated metal layer and the bonding layer. In addition, polyborosiloxane can be added to the coating slurry to increase the dispersibility of the coating slurry, and can also regulate the pore structure of the high-temperature coating bonding layer, improve the density, and help form micro-nano channels, expose more active sites, and enhance the adhesion of the electroplated metal layer. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Preparation Example
[0045] Preparation Example 1: A polyborosiloxane is prepared according to the following method:
[0046] Methyltrimethoxysilane and boric acid were mixed, wherein the molar ratio of boric acid to methyltrimethoxysilane was 0.3:1, the temperature was raised to 35°C, the mixture was stirred for 1 hour, and then the temperature was raised to 110°C, the reaction was continued for 6 hours, and the glue was obtained by filtration, and finally polyborosiloxane was obtained by drying and heat treatment. The heat treatment temperature was 200°C and the heat treatment time was 3 hours.
[0047] Example
[0048] Example 1, a high temperature electroplated ceramic mosaic, is prepared according to the following process steps:
[0049] S1 pretreatment: After the ceramic body is cleaned and dried, a UV coating is sprayed on the surface of the body, wherein the UV coating is obtained by mixing a polyurethane acrylate resin, a diaryliodonium salt and trimethacrylate in a mass ratio of 1:0.5:1, and the UV layer is formed after drying and curing, and the thickness of the UV layer is 10 μm to obtain a pretreated ceramic body;
[0050] S2. High temperature coating: spraying coating slurry on the obtained pretreated ceramic body UV layer, the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil and ferrous oxide in a mass ratio of 1:1.5:0.08, drying and removing water, and then firing at 850°C to form a high temperature coating bonding layer, the thickness of the high temperature coating bonding layer is 0.1 mm;
[0051] S3. Electroplating: The vacuum degree is adjusted to 10-3 mbar, and the ceramic body obtained in step S2 is subjected to metal titanium bombardment and adhesion on the surface of the high-temperature coating bonding layer by magnetron sputtering to form an electroplated metal layer, the thickness of the electroplated metal layer is 0.2 μm, wherein the magnetron sputtering temperature is 750°C, and the sputtering time is 60 min;
[0052] S4. Coloring: In a nitrogen atmosphere, the surface of the electroplated metal layer of the ceramic body obtained in step S3 is colored by magnetron sputtering metal titanium. The magnetron sputtering time is 3 minutes to form an electroplated coloring layer. The thickness of the electroplated coloring layer is 2 μm. Finally, a golden high-temperature electroplated ceramic mosaic is obtained.
[0053] Example 2, a high-temperature electroplated ceramic mosaic, differs from Example 1 only in that the UV coating is obtained by mixing a polyurethane acrylate resin, a diaryliodonium salt and trimethylacrylate in a mass ratio of 1:0.4:1.2; and the coating slurry is obtained by mixing a lead-free frit glaze, an aqueous oil and ferrous oxide in a mass ratio of 1:1.2:0.05.
[0054] Example 3, a high-temperature electroplated ceramic mosaic, differs from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil and ferrous oxide in a mass ratio of 1:1.8:0.1; the electroplated metal layer is a nickel layer; and the coloring step is carried out in an argon atmosphere to obtain a silver high-temperature electroplated ceramic mosaic.
[0055] Example 4, a high temperature electroplated ceramic mosaic, differs from Example 1 only in that an equal amount of manganese oxide is used to replace ferrous oxide.
[0056] Example 5, a high temperature electroplated ceramic mosaic, differs from Example 1 only in that ferrous oxide is replaced by an equal amount of a mixture of ferrous oxide and manganese oxide in a mass ratio of 1:1.
[0057] Example 6, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil and ferrous oxide in a mass ratio of 1:1.5:0.02.
[0058] Example 7, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil and ferrous oxide in a mass ratio of 1:1.5:0.15.
[0059] Example 8, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil, ferrous oxide and polyborosiloxane prepared in Preparation Example 1 in a mass ratio of 1:1.5:0.02:0.35.
[0060] Example 9, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil, ferrous oxide and polyborosiloxane prepared in Preparation Example 1 in a mass ratio of 1:1.5:0.02:0.3.
[0061] Example 10, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil, ferrous oxide and polyborosiloxane prepared in Preparation Example 1 in a mass ratio of 1:1.5:0.02:0.4.
[0062] Example 11, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil, ferrous oxide and polyborosiloxane prepared in Preparation Example 1 in a mass ratio of 1:1.5:0.02:0.2.
[0063] Example 12, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil, ferrous oxide and polyborosiloxane prepared in Preparation Example 1 in a mass ratio of 1:1.5:0.02:0.5.
[0064] Example 13, a high-temperature electroplated ceramic mosaic, is different from Example 1 only in that the coating slurry is obtained by mixing lead-free frit glaze and aqueous oil in a mass ratio of 1:1.5.
[0065] Comparative Example
[0066] Comparative Example 1, a high temperature electroplated ceramic mosaic, is prepared according to the following process steps:
[0067] S1. High temperature coating: After cleaning and drying the ceramic body, spray coating slurry, the coating slurry is obtained by mixing lead-free frit glaze, aqueous oil and ferrous oxide in a mass ratio of 1:1.5:0.08, drying and removing water, and then firing at 850°C to form a high temperature coating bonding layer, the thickness of the high temperature coating bonding layer is 0.1mm;
[0068] S2. Electroplating: Adjust the vacuum degree to 10 -3 mbar, the ceramic body obtained in step S1 is subjected to metal titanium bombardment adhesion on the surface of the high-temperature coating bonding layer by magnetron sputtering to form an electroplated metal layer, the thickness of the electroplated metal layer is 0.2 μm, wherein the magnetron sputtering temperature is 750°C and the sputtering time is 60 min;
[0069] S3. Coloring: In a nitrogen atmosphere, the surface of the electroplated metal layer of the ceramic body obtained in step S2 is colored by magnetron sputtering metal titanium. The magnetron sputtering time is 3 minutes to form an electroplated coloring layer. The thickness of the electroplated coloring layer is 2 μm. Finally, a golden high-temperature electroplated ceramic mosaic is obtained.
[0070] Comparative Example 2, a high temperature electroplated ceramic mosaic, is prepared according to the following process steps:
[0071] S1 pretreatment: After the ceramic body is cleaned and dried, a UV coating is sprayed on the surface of the body, wherein the UV coating is obtained by mixing a polyurethane acrylate resin, a diaryliodonium salt and trimethacrylate in a mass ratio of 1:0.5:1, and the UV layer is formed after drying and curing, and the thickness of the UV layer is 10 μm to obtain a pretreated ceramic body;
[0072] S2. Electroplating: Adjust the vacuum degree to 10 -3 mbar, the pre-treated ceramic body is subjected to magnetron sputtering, and metal titanium is bombarded and attached on the surface of the UV layer to form an electroplated metal layer, the thickness of the electroplated metal layer is 0.2μm, wherein the magnetron sputtering temperature is 750℃, and the sputtering time is 60min;
[0073] S3. Coloring: In a nitrogen atmosphere, the surface of the electroplated metal layer of the ceramic body obtained in step S2 is colored by magnetron sputtering metal titanium. The magnetron sputtering time is 3 minutes to form an electroplated coloring layer. The thickness of the electroplated coloring layer is 2 μm. Finally, a golden high-temperature electroplated ceramic mosaic is obtained.
[0074] Comparative Example 3, a high temperature electroplated ceramic mosaic, is prepared according to the following process steps:
[0075] S1. Electroplating: After cleaning and drying the ceramic body, adjust the vacuum degree to 10 -3 mbar, the ceramic body is subjected to magnetron sputtering, and titanium is bombarded and attached on the surface to form an electroplated metal layer, the thickness of the electroplated metal layer is 0.2μm, wherein the magnetron sputtering temperature is 750℃, and the sputtering time is 60min;
[0076] S2. Coloring: In a nitrogen atmosphere, the surface of the electroplated metal layer of the ceramic body obtained in step S1 is colored by magnetron sputtering metal titanium. The magnetron sputtering time is 3 minutes to form an electroplated coloring layer. The thickness of the electroplated coloring layer is 2 μm. Finally, a golden high-temperature electroplated ceramic mosaic is obtained.
[0077] Performance testing
[0078] Adhesion test:
[0079] (1) Use a grid knife to cut a cross-shaped grid on the surface of the high-temperature electroplated ceramic mosaic obtained in the embodiment and the comparative example, with a total of 8*8 squares, and cut until the ceramic body is cleaned with a soft brush and then pulled with 3M 600# tape 3 times, and the percentage of the area that has not fallen off to the total area is calculated;
[0080] (2) According to the relevant records in ASTM D4541-22 "Standard Test Method for Pull-off Adhesion Strength of Coatings Using a Portable Adhesion Tester", the pull-off adhesion strength of the high-temperature electroplated ceramic mosaic materials obtained in the examples and comparative examples was tested.
[0081] The above test results are shown in Table 1:
[0082] Table 1 Adhesion test results
[0083]
[0084] According to Table 1, in combination with Example 1 and Example 2 to Example 5, it can be seen that the non-detached area ratio and the pull-off adhesion strength of Example 2 to Example 5 are not much different from those of Example 1, indicating that the electroplating layer adhesion of Example 2 to Example 5 is not much different from that of Example 1. The reason is that the only change of Example 2 to Example 5 compared with Example 1 is that the raw materials and the raw material ratio are adjusted within the required range, which has little effect on the performance of the ceramic mosaic obtained in the end.
[0085] Combining Example 1, Example 6, Example 7 and Example 13, it can be seen that the percentage of non-detached area and the pull-off adhesion strength of Example 6, Example 7 and Example 13 are lower than those of Example 1, and the decrease in Example 13 is more obvious. The reason is that the amount of ferrous oxide added in the plating slurry used in Example 6 is reduced, and the binding force between the ferrous oxide and the metal ions decreases during the electroplating process, thereby causing the adhesion of the electroplated layer to decrease, while no ferrous oxide is added in Example 13, and the adhesion decreases more significantly. In Example 7, the amount of ferrous oxide added is increased, but the addition of excessive ferrous oxide is not conducive to particle dispersion, and will affect the pore structure of the high-temperature plating bonding layer, resulting in a decrease in metal ion penetration, and thus a decrease in adhesion.
[0086] Combining Example 1, Example 8, and Example 9 to Example 12, it can be seen that the pull-off adhesion strength of Example 8 is increased compared with Example 1. The reason is that polyborosiloxane is added to the coating slurry in Example 8, which can improve the dispersibility of the coating slurry, regulate the pore structure of the formed high-temperature coating bonding layer, improve the density of the film layer, expose more active sites, and be more conducive to the bonding of the electroplated metal layer. The performance of Example 9 and Example 10 is not much different from that of Example 8. The reason is that the difference between Example 9 and Example 10 and Example 8 is that the addition amount of polyborosiloxane is changed within the required range. The pull-off adhesion strength of Example 11 and Example 12 is slightly reduced compared with Example 8. The reason is that the addition amount of polyborosiloxane is reduced in Example 11, and the dispersion effect of the coating slurry and the ability to regulate the pores of the high-temperature coating bonding layer are reduced; the addition amount of polyborosiloxane is increased in Example 12, which will lead to a decrease in the number of pores, and the active sites are buried, which is difficult to combine with the electroplated metal ions, resulting in a slight decrease in adhesion.
[0087] Combining Example 1 and Comparative Examples 1 to 3, it can be seen that the non-detached area ratio and pull-off adhesion strength of Comparative Examples 1 to 3 are significantly reduced compared with Example 1. The reason is that the ceramic mosaic in Comparative Example 1 has not been treated with UV coating, and the impurities on the surface of the ceramic body will affect the bonding force between the high-temperature coating bonding layer and the ceramic body, and also reduce the reactivity of the surface of the ceramic body, thereby causing the overall adhesion performance to decrease; Comparative Example 2 has not been treated with coating slurry spraying, and it is difficult for the electroplated metal layer to form a tight connection with the UV layer, and there is no intercalation effect of the pore structure, resulting in a significant decrease in the adhesion of the ceramic mosaic; Comparative Example 3 has neither been treated with UV coating nor with coating slurry spraying, and the adhesion decrease is more obvious.
[0088] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for high temperature electroplating ceramic mosaic, characterized in that: The process steps include: S1. Pretreatment: After the ceramic body is cleaned and dried, a UV coating is sprayed on the surface of the body, and a UV layer is formed after drying and curing to obtain a pretreated ceramic body; S2. High temperature coating: spray coating slurry on the obtained pre-treated ceramic body UV layer, dry and remove water, and then perform high temperature firing, the high temperature firing temperature is 800-900°C, to form a high temperature coating bonding layer; the raw materials of the coating slurry include frit, aqueous oil, metal oxide and polyborosiloxane in a mass ratio of 1: (1.2-1.8): (0.05-0.1): (0.3-0.4); the metal oxide is iron and / or manganese oxide; S3. Electroplating: Under vacuum conditions, the ceramic body obtained in step S2 is subjected to magnetron sputtering, wherein the magnetron sputtering temperature is 600 to 800° C., and metal bombardment and adhesion are performed on the surface of the high-temperature coating bonding layer to form an electroplated metal layer; S4. Coloring: By controlling the type of electroplating auxiliary gas, the surface of the electroplated metal layer of the ceramic body obtained in step S3 is colored by magnetron sputtering metal titanium to form an electroplated coloring layer, and finally a high-temperature electroplated ceramic mosaic is obtained.
2. The production process of high temperature electroplating ceramic mosaic according to claim 1, characterized in that: The vacuum degree in the S3 electroplating step is 10 -3 ~10 -7 mbar, and the sputtering time is 40 to 90 minutes.
3. The production process of high temperature electroplating ceramic mosaic according to claim 1, characterized in that: The raw materials of the UV coating include UV paint, a photoinitiator and a diluent in a mass ratio of 1: (0.4-0.5): (1-1.2).
4. The production process of high temperature electroplating ceramic mosaic according to claim 1, characterized in that: The frit is a lead-free frit glaze.
5. The production process of high temperature electroplating ceramic mosaic according to claim 1, characterized in that: The metal layer in the S3 electroplating step is one of a titanium layer, a nickel layer, a cobalt layer and an iron layer.
6. The production process of high temperature electroplating ceramic mosaic according to claim 1, characterized in that: The auxiliary gas includes one of oxygen, argon and nitrogen.
7. A high temperature electroplated ceramic mosaic, characterized in that: The high temperature electroplating ceramic mosaic is produced according to the production process of any one of claims 1 to 6.
Citation Information
Patent Citations
UV ink-jet mosaic process for glass electroplating metal surface
CN111606738A
Surface metallization process of dielectric ceramic filter
CN112779494A
Multilayer gradient coating based on physical vapor deposition and preparation method thereof
CN113930725A